2009
DOI: 10.4103/0971-3026.50839
|View full text |Cite
|
Sign up to set email alerts
|

Deferiprone-induced arthropathy in thalassemia: MRI findings in a case

Abstract: Arthropathy is a well known side effect of the iron chelator deferiprone (L1); however, the imaging findings in deferiprone-induced arthropathy are not well known. In this article, we describe the typical radiographic and MRI findings in a patient receiving regular blood transfusions who developed arthropathy after long-term therapy with the oral iron chelator deferiprone (L1). Deferiprone primarily affects the articular cartilage and the changes include synovial thickening, articular cartilage thickening, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The knee radiograph showed subchondral flattening of femoral and tibial condyles with irregular articular margins. Previous reports of deferiprone arthropathy have shown joint effusions, articular cartilage destruction, subchondral bone changes consisting of irregularity and flattening and patellar beaking in the knee joint . In one study, based on MRI findings, these changes were seen in 12 out of 14 patients (86%) on deferiprone and the degree of abnormality did not reflect the severity of symptoms .…”
Section: Discussionmentioning
confidence: 90%
“…The knee radiograph showed subchondral flattening of femoral and tibial condyles with irregular articular margins. Previous reports of deferiprone arthropathy have shown joint effusions, articular cartilage destruction, subchondral bone changes consisting of irregularity and flattening and patellar beaking in the knee joint . In one study, based on MRI findings, these changes were seen in 12 out of 14 patients (86%) on deferiprone and the degree of abnormality did not reflect the severity of symptoms .…”
Section: Discussionmentioning
confidence: 90%
“…The administering doctor stopped the DFP for Included in the study 3 months and the symptoms subsided. 5 A second case study by Tewari et al 11 reported a possible periodontal manifestation of agranulocytosis caused by DFP. This patient complained of grayish-white discoloration of his gingiva, followed by tooth pain.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were appraised using the appropriate JBI critical appraisal tools ( Table 5). 4 Neutropenia, agranulocytosis, increased ALT, gastrointestinal problem, arthralgia/ arthropathy, increased weight Chand et al 5 Arthralgia/arthropathy Cohen et al 7 Neutropenia, agranulocytosis, increased ALT, gastrointestinal problem, arthralgia/ arthropathy, increased in appetite/weight, thrombocytopenia…”
Section: Resultsmentioning
confidence: 99%
“…MRI results present in DFP-related arthropathy are synovial thickening, articular cartilage thickening, and subchondral bone erosions. 5 Increased in appetite/weight Weight gain has been identified as an effect of DFP consumption. Even though two studies included observations on weight increase, there were no details regarding how much weight was gained or whether it was statistically significant.…”
Section: Arthralgia/arthropathymentioning
confidence: 99%